Influence of natural plantations with participance of velvetweed oak on soil fertility - Rafalska, L. P. (Land Management, Cadastre and Land Monitoring, 2017)
According to research in natural 31‐167 annual overgrown plantations of velvetweed oak established that in soil of mixed forest plantation more humus and nitrogen compared with pure. On the content of phosphorus and potassium certain regularity was not found.